Thematic-integrative-based pictorial book for improving the understanding reading skills of elementary school students - Ade Gunawan; Suhardi Suhardi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
The study aims at composing a picture book using the thematic-integrative approach that might improve the reading comprehension skills of the Grade IV students. With regards to the conduct of the study, the initiative that has been taken is research and development (RD). Within this initiative, product development refers to the model that has been developed by Borg Gall. Then, throughout the conduct of the study, 19 students had been involved as the field subjects and the data had been gathered by means of guided interview technique, observation, product fitness questionnaire, teacher and student response questionnaire and reading comprehension skills test. Furthermore, the product effectiveness had been tested by means of the quasi-experiment method and the data had been analysed by using the paired sample t-test with a significant rate of 0.05. The results of the study show that: (1) the thematic-integrative-based picture book has been fit for implementation as learning media based on the “Very Good” category that has been assigned by the media expert and the “Good” category by the material expert; and (2) the thematic-integrative-based picture book has been effective in improving the reading comprehension skills as having been confirmed by the improvement from the mean score 72.11 in the pre-test results into the mean score 81.63 in the post-test results. The improvement in the students’ reading comprehension skills has been shown by the significance value (p) 0.000. In addition, based on the paired-sample t-test it is found that p 0.05. This value indicates that the thematic-integrative-based picture book has a significant influence on the improvement of reading comprehension skills among Grade IV students.